Biaxial Compression Tests on Hopkinson Bars - Bastien Durand (Proceedings, 2018)
A biaxial compression Hopkinson bar set-up bas been designed. It consists in a projectile, an input bar and two co-axial output bars. After the projectile impact on the input bar, the internal output bar measures the axial loading of the cross sample whereas the external output bar measures its transversal loading via a mechanism with sliding surfaces. Gauges glued on the bars enable stain measurements which lead to the forces and to the displacements on the interfaces between the bars and the mounting. The displacement field of the sample is obtained by high-speed imaging and by digital image correlation. Experiments show that the set-up works despites two disadvantages. Firstly, the transversal force in the sample is over-estimated because of the friction in the mechanism. Moreover, comparisons between the displacements on the bars interfaces and the sample displacement field display that the clearance have an influence on the sample loading.